Initial psychometric properties of the Parental Stress Scale examined using a sample of Russian mothers - Bochaver, Alexandra A.; Akhmedjanova, Diana R.; Bayramyan, Roksana M.; Fomicheva, Elizaveta V. (Frontiers in Psychology, 2023)
Parental stress is defined as a personal response to stressors associated with being a parent. In recent studies, parental stress has been viewed as a component of normative parenting. The purpose of this study was to collect initial evidence of the construct validity and reliability of the Russian version of the 18-item Parental Stress Scale (PSS) using a sample of mothers of Russian primary school students. The results are the first wave of a longitudinal study. Mothers (n = 900) of fourth-grade students participated in the study and filled out an online survey. The exploratory and confirmatory factor analyses of the PSS on the Russian mothers indicated two factors: parental stress and parental satisfaction, with good estimates of reliability. The PERMA-Profiler questionnaire was used to examine the convergent and divergent validity of the PSS. The results revealed significant correlations between parental stress and satisfaction and different aspects of well-being among the respondents. The initial investigation of this Russian adaptation of the PSS provides evidence of its reliability and validity. Despite the limitations and the need for further research, this version of the PSS can be recommended for use in studies on modern parenting as well as in psychological support, education, and development of programs promoting positive parent-child relationships by targeting parental needs.